2016
DOI: 10.7717/peerj.2450
|View full text |Cite
|
Sign up to set email alerts
|

Tissue and serum samples of patients with papillary thyroid cancer with and without benign background demonstrate different altered expression of proteins

Abstract: BackgroundPapillary thyroid cancer (PTC) is mainly diagnosed using fine-needle aspiration biopsy. This most common form of well-differentiated thyroid cancer occurs with or without a background of benign thyroid goiter (BTG).MethodsIn the present study, a gel-based proteomics analysis was performed to analyse the expression of proteins in tissue and serum samples of PTC patients with (PTCb; n = 6) and without a history of BTG (PTCa; n = 8) relative to patients with BTG (n = 20). This was followed by confirmati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 41 publications
1
15
0
1
Order By: Relevance
“…17 In a recent study, lower levels of APOA4 in the benign class compared to PTC were observed, which contrasts with our results. 18 However, in line with our findings, in many cancers, decreased levels of APOA4 was observed. For example, Jeong et al 19 found lower APOA4 as a marker for squamous cell carcinoma of uterine cervix.…”
Section: Discussionsupporting
confidence: 91%
“…17 In a recent study, lower levels of APOA4 in the benign class compared to PTC were observed, which contrasts with our results. 18 However, in line with our findings, in many cancers, decreased levels of APOA4 was observed. For example, Jeong et al 19 found lower APOA4 as a marker for squamous cell carcinoma of uterine cervix.…”
Section: Discussionsupporting
confidence: 91%
“…113. In addition, overexpression of alpha1-antitrypsin (A1AT) in PTC tissue samples was also reported in three separate studies 14, 110, 111.…”
Section: Proteome-based Ptc Biomarkersmentioning
confidence: 76%
“…In the present study, CCDC25 expression in cancerous tissues, as determined by immunohistochemistry, was correlated with serum CCDC25 level, suggesting that CCA cells are the major source of CCDC25 in the sera. Certain studies have reported that protein levels in serum samples may differ from protein expression levels in tissue due to a modification process during protein translocation (28,29). Therefore, to further validate that serum CCDC25 is mainly derived from CCA tissue, the association of serum and tissue CCDC25 expression levels should be verified using a larger number of paired samples.…”
Section: Discussionmentioning
confidence: 99%